Impact of Goods And Services Tax on Indian Economy - Dr. H. B. Gupta (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2016)
The Goods and Service Tax (GST) is a one of the most important taxation reform in India which is set to create a single unified Indian market. GST is a consumption based tax. It imposed on sale, manufacture and consumption of goods & services. This tax will be replaced all indirect tax imposed by state and central government. GST would apply to all goods except crude petroleum, motor spirit, diesel, aviation turbine fuel and natural gas. It would apply to all services barring a few to be specified. The proposed tax system will take the form of “dual GST” which will concurrently be levied by central and state government. The main reason to implement GST is to abolish the cascading effect on tax. The GST is already implemented more than 140 countries. France was first country in the world, who implemented GST. International experience suggests that GST would improve tax collections in a seamless manner and spur the economic growth about 0.9% to1.75%. It is expected that GST will minimize leakage and also eliminate the litigations arising out of the predicament of dual levies of VAT and Service tax. This paper is focuses on analyzing the proposed tax structure and its impact on Indian Economy.